The Rhetoric of Ableism - James L. Cherney (Disability Studies Quarterly, 2011)
This essay argues that rhetoric is both the means by which ableist culture perpetuates itself and the basis of successful strategies for challenging its practices. Public demonstrations, countercultural performances, autobiography, transformative histories, and critiques of ableist films and novels all apply rhetorical solutions to the problem of ableism. The study employs Kenneth Burke's theory of identification and Stuart Hall's configuration of ideology to uncover those commonplace "languages of practical thought" that generate and sustain ableist perspectives and ideas. Focusing on the rhetoric of ableism at the level of the warrants used to interpret disability, this article closely examines the way Aristotle's Generation of Animals relies on the equivocation "normal is natural."
Keywords: Ableism; Aristotle; identification; Kenneth Burke; rhetoric; Stephen Toulmin; warrants